Strategi Pengembangan Pariwisata Hijau: Urgensi Regulasi dan Sinergi Multisektoral di Kota Ambon - Hunihua, Reina Iriene; Suat, Hatty (Universitas Pattimura, 2023)
The development of green tourism in Ambon City has become an urgent necessity in addressing environmental challenges and the sustainability of the tourism sector. However, the existing policies have not yet provided specific regulations to support the implementation of this concept. This study aims to analyze green tourism development strategies through a regulatory approach and multisectoral synergy. The research employs a qualitative method, including policy studies, interviews with stakeholders, and an analysis of best practices in sustainable destination management. The findings indicate that the absence of comprehensive regulations hinders the optimization of green tourism potential in Ambon. Therefore, a cross-sectoral policy approach is required, involving the government, tourism industry players, tourism-conscious communities, and academics in formulating adaptive and participatory strategies. This synergy is expected to enhance the competitiveness of Ambon City's tourism sector, encourage sustainable investment, and positively impact community welfare. This study contributes to the development of social sciences and humanities, particularly in sustainable tourism policy, and serves as a reference for local governments in formulating more inclusive policies to establish Ambon as a leading green tourism destination in Maluku.